Interkinetic nuclear migration generates and opposes ventricular-zone crowding: insight into tissue mechanics - Miyata, Takaki; Okamoto, Mayumi; Shinoda, Tomoyasu; Kawaguchi, Ayano (Frontiers in Cellular Neuroscience, 2015)
The neuroepithelium (NE) or ventricular zone (VZ), from which multiple types of brain cells arise, is pseudostratified. In the NE/VZ, neural progenitor cells are elongated along the apicobasal axis, and their nuclei assume different apicobasal positions. These nuclei move in a cell cycle–dependent manner, i.e., apicalward during G2 phase and basalward during G1 phase, a process called interkinetic nuclear migration (INM). This review will summarize and discuss several topics: the nature of the INM exhibited by neural progenitor cells, the mechanical difficulties associated with INM in the developing cerebral cortex, the community-level mechanisms underlying collective and efficient INM, the impact on overall brain formation when NE/VZ is overcrowded due to loss of INM, and whether and how neural progenitor INM varies among mammalian species. These discussions will be based on recent findings obtained in live, three-dimensional specimens using quantitative and mechanical approaches. Experiments in which overcrowding was induced in mouse neocortical NE/VZ, as well as comparisons of neocortical INM between mice and ferrets, have revealed that the behavior of NE/VZ cells can be affected by cellular densification. A consideration of the physical aspects in the NE/VZ and the mechanical difficulties associated with high-degree pseudostratification (PS) is important for achieving a better understanding of neocortical development and evolution.